Effects of thoracic posture correction exercises on scapular position - Yoo, Won-gyu (J Phys Ther Sci, 2018)
[Purpose] The purpose of this study was to investigate the effects of thoracic extension exercise on scapular alignment and thoracic kyphosis angle. [Subjects and Methods] Ten subjects with a kyphosis angle ≥40° and aged between 20 and 26 years participated in this study. This study investigated the scapular forward distance and thoracic kyphosis angle before and after the thoracic extension exercise. [Results] The kyphosis angle after exercise was significantly decreased compared with that before exercise. Scapular forward distance after exercise significantly decreased compared to that before exercise. [Conclusion] The results of the present study suggest that correction of thoracic kyphosis should be included among exercises designed to achieve normal scapular alignment.